Efficiency of linear accelerators for applied aims - Lymar, A.G.; Sokolenko, E.N.; Khizhnyak, N.A. (Вопросы атомной науки и техники, 2001)
As it is well known the accelerator efficiency as a whole η is the product of the efficiency of an accelerator itself ηa and the efficiency of its power feed system ηf : η = ηa ∙ ηf. There are many papers in which the value of ηa is considered but the value of ηf is studied worse. This paper is the review of the works concerning the increase of ηf in dependence on a chosen high-frequency power system of the accelerator. In this case both linear electron accelerators and proton radio-frequency accelerators are considered. In initial versions the accelerator was considered as a system consisting of two subsystems: i.e. the power supply system and the accelerating structure itself. It was supposed that ηf is determined by a product of the generator efficiency multiplied by the feeding system efficiency. Separately created was r.f. generator with a high electronic efficiency and the feeding system was improved. Last time the tendency appeared when the feeding system was degenerated practically and r.f. power system of the accelerator was the component structure of the accelerator itself. Let consider the evolution of r.f. power system on examples of electron and proton accelerators.